Caritas: organização da sociedade civil efetivando direitos humanos - Silva, Alan Faria Andrade (2019)
The increasing number of displaced people in the world is estimated due to the severe fear of persecution, through war and conflict. In Brazil alone, for the last 8 years, there were more than 60,000 people seeking a refugee status. Another important figure is that, currently, there are 820,000 entities, which compose civil society organizations, called third sector organizations. Given that, it can also be observed that the Reference Center for Refugees of Caritas Arquidiocesana de São Paulo can assist, on average, from 2,000 to 3,000 people forced to move. This entity, being an organism of the Catholic Church, in the city of São Paulo, is a civil society entity, being recognized as a Civil Society Organization, which responds to the requests of these people who are required to migrate. Therefore, this investigation has as its objective to develop the observation of the reality in ‘Caritas’. The study sought to construct a reflective, analytical and descriptive path for these activities, as well as the legal framework as a non-profit association, going through existing certifications and partnerships. Finally, it has sought to understand the concepts of civil society, human rights, the right to refuge and the effectiveness of the Law. The methodology applied to the development of this work was based on data collection techniques through documentary research. It has been found that the word ‘Caritas’ itself is provided with the charitable animus for exercising the entity activities. Researches revealed that the Reference Center is simply a support place, where asylum seekers and refugees seek services such as legal guidance, healthcare and basic care, as well as their integration, through education and work. It was also proved that, as a result, the center could contribute to the internalization of the United Nations Convention Relating to the Status of Refugees in 1951, causing the creation of the Brazilian Refugee Act (Law 9,474 of 1997) and the country’s participation in NCFR. In addition, through the agreement reached with UNHCR, the institution's activities are concentrated in the working areas of protection, assistance and integration. Also, through legal documents and other available documents for the research, it can be concluded that ‘Caritas’ is a non-profit association which promotes social assistance, being characterized as a third sector entity, currently recognized as a civil society organization, by exercising the right to freedom of association. Moreover, the third sector can be seen as an object of study of Diffuse and Collective Rights. Finally, it has also been found that these type of entities are new democracy arenas and a source of effectiveness of rights. Caritas, through the Reference Center for Refugees, implements human rights, in the perspective of protection, assistance and integration; areas of strong implementation of its agents who welcome, guide and assist people who seek survival and hope to move on to a new place, in the city of São Paulo